A lost generation? Long term socioeconomic outcomes in orphans - Carlos Bozzoli (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
Previous research on orphanhood has established that parental death has a negative effect in terms of school enrollment and grade progression, but the relation between orphanhood and socioeconomic outcomes in young adults has been largely ignored in the literature. In this paper, I use a longitudinal survey from the city of Cape Town, South Africa to evaluate two main outcomes of young adults, namely labor market attachment and fertility, and its relation to orphanhood status. The uniqueness of this dataset lies within the combination of different survey waves with a year-by-year life history that records key outcomes (e.g. schooling, work, fertility outcomes). It also provides information on so-called parental investments (time and material support),family background, and literacy and numeracy test scores. I find that although preexisting parental background characteristics and literacy and numeracy skills are comparable between orphans and non-orphans, the latter are less likely to be employed(true primarily for males) or to have children (females) early in their lives. Evidence ismixed regarding whether orphans earn lower wages than non-orphans. These results suggest that orphanhood may not only alter educational achievements, but that it may also leave a long-lasting imprint in terms of employment and fertility patterns.
Keywords: J12; J13; J22; O12; 330; Orphans; employment; wages; fertility; parental investments; Jugendliche; Familiensoziologie; Erwerbstätigkeit; Fruchtbarkeit; Südafrika